Acupuncture and women's health: an overview of the role of acupuncture and its clinical management in women's reproductive health - Cochrane S; Smith CA; Possamai-Inesedy A; Bensoussan A (Dove Medical Press, 2014)
Suzanne Cochrane,1 Caroline A Smith,2 Alphia Possamai-Inesedy,3 Alan Bensoussan2 1School of Science and Health, 2Centre for Complementary Medicine Research, 3School of Social Sciences and Psychology, University of Western Sydney – Campbelltown Campus, Penrith, NSW, Australia Background: Acupuncture and other modalities of Chinese/East Asian medicine have been used to treat women's health for many centuries. Gynecology specialties focus particularly on menstrual and reproductive disorders. Both the adoption of the use of acupuncture outside Asia, and the incorporation of scientific analysis in Asia have challenged biomedical conceptions of what can be achieved with this treatment method. The scale of research activity in relation to acupuncture and women's health has increased over the last 20 years. Objective: This review aims to explore the research evidence in relation to acupuncture use for women's reproductive disorders, focusing on both clinical findings and experimental research on acupuncture's mechanisms of action in relation to women's health. Methods: A narrative literature search was undertaken using searches of electronic databases and manual searches of journals and textbooks. The search included all literature published prior to June 2013. The literature was assessed as to the nature of the study it was reporting and findings synthesized into a commentary. Results: For acupuncture's mechanism of action the search resulted in 114 relevant documents; in relation to clinical reports on the use of acupuncture for women's health 204 documents were found and assessed. Conclusion: There is preliminary data indicating acupuncture may improve menstrual health and coping for women experiencing delays falling pregnant. There is experimental data showing that acupuncture can influence female reproductive functioning, although the actual mechanisms involved are not yet clarified. Further well-conducted clinical research would benefit our understanding of the usefulness of acupuncture to women's health. Keywords: reproductive disorders, women, health, Chinese medicine, alternative medicine, acupuncture